Autoimmune hepatitis treatment in the elderly: A systematic review - Durazzo, Marilena (World J Gastroenterol, 2019)
BACKGROUND: Autoimmune hepatitis (AIH) is a rare chronic inflammatory liver disease with a high risk of progression to liver cirrhosis. The initial treatment for AIH usually includes a steroid, with or without azathioprine. AIH can present at any age; however, the most effective and safe induction treatment for AIH in the elderly remains unclear. AIM: To systematically review available data on both effectiveness and safety of AIH treatments in elderly subjects. METHODS: To identify studies on AIH induction treatment in elderly patients (≥ 60 years of age), an electronic research was performed (PubMed, EMBASE and Cochrane Library databases) until February 2019. Eligible studies were selected through screening of titles and abstracts, followed by full-text critical evaluation. After risk of bias assessment, data on study designs, interventions, and outcomes were extracted and reviewed. RESULTS: Among the 1736 retrieved papers, 15 studies were selected. Out of them, eight studies were excluded because of a critical risk of bias. The remaining seven studies included 789 patients and out of them 239 subjects were elders. First-line treatment was a steroid either alone or in combination with azathioprine in most patients (87.6%) and only one study investigated the effect of combined steroid and mycophenolate mofetil therapy. Standard therapy was effective in inducing remission in the elderly. Moreover, treatment failure and relapses occurred less often in the elderly compared to younger people. CONCLUSION: Treatment of AIH is challenging in elderly patients. This systematic review confirms the efficacy and safety of standard induction treatment for AIH in the elderly. Available evidence is insufficient to draw any conclusion on the effect of novel AIH treatments in elderly subjects.